Incorporation of [(3)H]Leucine and [(3)H]Valine into Protein of Freshwater Bacteria: Uptake Kinetics and Intracellular Isotope Dilution - Jørgensen, Niels O. G. (1992)
Incorporation of [(3)H]leucine and [(3)H]valine into proteins of freshwater bacteria was studied in two eutrophic lakes. Incorporation of both amino acids had a saturation level of about 50 nM external concentration. Only a fraction of the two amino acids taken up was used in protein synthesis. At 100 nM, the bacteria respired 91 and 78% of leucine and valine taken up, respectively. Respiration of (3)H and (14)C isotopes of leucine gave similar results. Most of the nonrespired leucine was recovered in bacterial proteins, while only up to one-half of the nonrespired valine occurred in proteins. In intracellular pools of the bacteria, [(3)H]leucine reached an isotope saturation of 88 to 100% at concentrations of >40 nM. For [(3)H]valine, an isotope equilibrium of about 90% was obtained at concentrations of >80 nM. Within an incubation period of typically 1 h, tritiated leucine and valine incorporated into proteins of the bacteria reached an isotope saturation of 2 to 6%. In a 99-h batch experiment, bacterial protein synthesis calculated from incorporation of leucine and valine corresponded to 31 and 51% (10 nM) and 89 and 97% (100 nM), respectively, of the chemically determined protein production. Measured conversion factors of 100 nM leucine and valine were 6.4 × 10(16) and 6.6 × 10(16) cells per mol, respectively, and fell within the expected theoretical values. The present study demonstrates that incorporation of both valine and leucine produces realistic measurements of protein synthesis in freshwater bacteria and that the incorporation can be used as a measure of bacterial production.